A mitovirus related to plant mitochondrial gene confers hypovirulence on the phytopathogenic fungus Sclerotinia sclerotiorum - Xu, Zhiyong; Wu, Songsong; Liu, Lijiang; Cheng, Jiasen; Fu, Yanping; Jiang, Daohong; Xie, Jiatao (Virus research, 2015)
•We report a novel mitovirus strain, SsMV1/HC025, isolated from a hypovirulent strain of Sclerotinia sclerotiorum.•We determined the full-length sequence of SsMV1/HC025, which has a genome comprising 2530 nucleotides.•SsMV1/HC025 confers hypovirulence on S. sclerotiorum.•Mitovirus RdRp gene was evolutionarily related to plant mitochondrial genome. A double-stranded RNA (dsRNA) segment was isolated from a hypovirulent strain, HC025, of Sclerotinia sclerotiorum. The complete nucleotide sequence of the dsRNA was determined to be 2530bp in length. Using the fungal mitochondrial genetic code, the positive strand of the dsRNA was found to contain a single large open reading frame (ORF) with the characteristic conserved motifs of the RNA-dependent RNA polymerase (RdRp). BLAST analysis revealed that RdRp shares 74% sequence identity with Sclerotinia sclerotiorum mitovirus 1 (SsMV1/KL-1). The positive strand of the dsRNA could be folded into potentially stable stem-loop structures at both the 5′ and 3′ terminal sequences. Moreover, the 5′ and 3′ terminal sequences were inverted complementary sequences and formed a panhandle structure. These results reveal that this dsRNA segment represents the replicative form of a mitovirus that is a strain of SsMV1 from the genus Mitovirus in the family Narnaviridae and was tentatively designated as Sclerotinia sclerotiorum mitovirus 1 (SsMV1/HC025). Sequence comparison and phylogenetic analysis suggest that mitovirus RdRp gene was evolutionarily related to plant mitochondrial genome. Our results demonstrate that SsMV1/HC025 infection exerted obvious effects on host biological properties. Hypovirulence feature and SsMV1/HC025 could be co-transmitted from hypovirulent strains to other virulent strains via hyphal contact. Thus, SsMV1/HC025 related to plant mitochondrial gene confers hypovirulence on S. sclerotiorum.